Phenetic analysis of wild populations of Momordica charantia L. (Cucurbitaceae) in West Africa and inference of the definition of the new subspecies macroloba Achigan-Dako & Blattner - Achiga, Enoch Gbenato; N'Danikou, Sognigbé; AHANCHEDE, ADAM; GANGLO, COSSI JEAN; BLATTNER, Franck R. (My University, 2008)
Momordica charantia L. (Cucurbitaceae) is a paleotropical species used as medicinal plant or vegetable in West Africa. This paper examines the morphological variation within some wild populations of Momordica charantia in the West African phytogeographical regions. The results point out that ecological conditions affect leaf size in that species, as well as the size of male and female bracts and peduncle lengths of that species. However, characters linked to the fruit size are uniform across regions except for pericarp thickness and tubercle height. The location of the bract on the peduncle is independent of environmental conditions. Multivariate analyses clarifies also the long-standing ambiguity for the identification of Momordica charantia observed in Benin by clearly discriminating two taxonomical groups based on the leaf lobe characters, the common subspecies charantia and the new subspecies Momordica charantia subsp. macroloba Achigan-Dako & Blattner endemic to the Dahomey gap and the Sudano-Guinean phytoregion of Benin and Togo. Phenetic analysis of wild populations of Momordica charantia L. (Cucurbitaceae)... | Request PDF. Available from: https://www.researchgate.net/publication/263239481_Phenetic_analysis_of_wild_populations_of_Momordica_charantia_L_Cucurbitaceae_in_West_Africa_and_inference_of_the_definition_of_the_new_subspecies_macroloba_Achigan-Dako_Blattner [accessed Mar 17 2018].